DOI: 10.15368/theses.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

An Investigative Study of Gurney Flaps on a NACA 0036 Airfoil

Abstract: This project examined the effect of Gurney flaps on a 2D, 2-ft chord NACA 0036 airfoil in the Cal Poly 3"x4" low speed wind tunnel at 25 m/s. It also covered the numerical simulation of the experiment in computational fluid dynamics (CFD). During the study, problems with the wind tunnel data were seen. After a careful diagnosis, the problem was traced to dirty flow conditioners which were subsequently replaced.Five Gurney flaps at 1, 2, 3, 4, and 5% of the chord were tested. The Gurney flaps had the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The study concluded that increase in the size of the Gurney flap leads to an increase in the lift coefficient for the sizes tested, also, it was noticed from the obtained data that the relationship between flap size and lift-curve shift does not seem to be linear. As an example, the increase in the lift coefficient between 0% and 0.5% chord length of the Gurney flap is higher than the increase in the lift coefficient due to changing the size of the Gurney flap from 1.5% and 2% chord length [6]. Adding a Gurney flap to the trailing edge of the wing not only increase the lift, but it also has a positive effect on delaying the separation on the suction surface.…”
Section: Introductionmentioning
confidence: 93%
“…The study concluded that increase in the size of the Gurney flap leads to an increase in the lift coefficient for the sizes tested, also, it was noticed from the obtained data that the relationship between flap size and lift-curve shift does not seem to be linear. As an example, the increase in the lift coefficient between 0% and 0.5% chord length of the Gurney flap is higher than the increase in the lift coefficient due to changing the size of the Gurney flap from 1.5% and 2% chord length [6]. Adding a Gurney flap to the trailing edge of the wing not only increase the lift, but it also has a positive effect on delaying the separation on the suction surface.…”
Section: Introductionmentioning
confidence: 93%
“…For a complete description of the inlet remanufacture, see the Appendices of Greg Altmann's paper. 13 Following the completion of the new flow straightener, the flow quality of the wind tunnel was measured. 14 The project was a senior project by three students.…”
Section: Cal Poly Wind Tunnel Recent Modificationsmentioning
confidence: 99%
“…Greg Altmanns's wind tunnel test (19) , previous to any of the Goldschmied testing, found that they were getting results that…”
Section: Recent Tunnel Modificationsmentioning
confidence: 99%
“…The standard k -ε model can be seen below: ( 18 ) and ( 19 ) where is the generation of turbulent kinetic energy due to velocity gradients, is generation due to buoyancy kinetic energy, and is the contribution of fluctuating dilatation in compressible turbulence. The standard k -ε model has weakness that has led to modifications to improve the model.…”
Section: K -ε Modelmentioning
confidence: 99%